Cytotoxicity of VCO Microemulsion Developed Using Non-Ionic Surfactants Mixture against Normal L6 Cell and Optimisation its Formulation Containing Curcumin - Kharis Zahid; Nadia Halib; Ishak Ahmad; Zainah Adam; Razali Mirad (Universiti Sains Islam Malaysia, 2024)
The objective of the study was to evaluate the properties of curcumin formulated in Virgin Coconut Oil (VCO) microemulsion system developed using food-acceptable grade surfactants of Tween 80, Span 80 and Span 40. Cytotoxicity analysis was carried out toward VCO microemulsion using normal L6 cells in vitro. The microemulsion was formulated using VCO as the oil phase with non-ionic surfactants mixture consist of Tween 80, Span 80 and Span 40. Curcumin was incorporated into VCO microemulsion as a cold mixture under mild agitation to form curcumin microemulsion. The physical stability of curcumin microemulsion was investigated and its characterisations were further studied according to its appearance (visual), morphology, turbidity, pH, droplet size, viscosity, conductivity, and polydispersity index. Based on the results of optimisation studies, the final 0.1 % (w/w) of curcumin concentration was successfully loaded into VCO microemulsion system. This formulation had clear transparent yellow curcumin colour without phase separation. The results indicated that the curcumin microemulsion had an average particle size about 43.15 nm and good stability with zeta potential -0.24 mV. The curcumin micoemulsion morphology had spherical in shape when observed under transmission electron microscopy (TEM), the curcumin microemulsion was slightly acidic with pH value 5.28, the conductivity was 241.2 ?S/cm and the viscosity was 8.5 cP.